2017
DOI: 10.1021/acschemneuro.7b00216
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Dependent Switch from RXR Homo- to RXR-NURR1 Heterodimerization

Abstract: Retinoid X receptors (RXRs) play key roles in many physiological processes in both the periphery and central nervous system. In addition, RXRs form heterodimers with other nuclear receptors to exert their physiological effects. The nuclear receptor related 1 protein (NURR1) is particularly interesting because of its role in promoting differentiation and survival of dopamine neurons. However, only a small number of RXR-heterodimer selective modulators are available, with limited chemical diversity. This work de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 50 publications
0
14
0
3
Order By: Relevance
“…Heterodimer- and subtype-specific targeting has been proposed as a strategy to overcome this, yet high sequence similarity between the three human RXR isoforms presents a challenge for the design of such selective modulators. Several examples demonstrate that RXR ligands can exhibit heterodimer preference (e.g., for RXR:PPAR [ 31 , 38 , 39 , 40 ], RXR:LXR [ 41 ] and RXR:Nurr1 [ 42 ]) and even subtype preference [ 30 , 31 ] but while some structural insights in heterodimer-preference mechanisms are available, subtype preference among RXRs remains elusive. As a basis for better understanding of the three RXR isoforms and potential selectivity mechanisms, we presented here a uniform set of the crystal structures for all three RXR isoform LBDs in activated conformation, providing improved structural insights for the design of RXR modulators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterodimer- and subtype-specific targeting has been proposed as a strategy to overcome this, yet high sequence similarity between the three human RXR isoforms presents a challenge for the design of such selective modulators. Several examples demonstrate that RXR ligands can exhibit heterodimer preference (e.g., for RXR:PPAR [ 31 , 38 , 39 , 40 ], RXR:LXR [ 41 ] and RXR:Nurr1 [ 42 ]) and even subtype preference [ 30 , 31 ] but while some structural insights in heterodimer-preference mechanisms are available, subtype preference among RXRs remains elusive. As a basis for better understanding of the three RXR isoforms and potential selectivity mechanisms, we presented here a uniform set of the crystal structures for all three RXR isoform LBDs in activated conformation, providing improved structural insights for the design of RXR modulators.…”
Section: Discussionmentioning
confidence: 99%
“…This notion was in line with previous structure–activity relationship studies on biphenyl-based RXR agonists [ 31 ], where an introduction of bulkier moieties at the terminal ring or substituents at the ortho position of the phenylacetic acid motif binding in the vicinity of helix 5, which forms an interface with helix 8, was observed to result in different affinities to the three RXR isoforms. In addition, various RXR-ligand complexes, including RXRα-LG100754 (PDB ID: 6sti) [ 43 ], RXRα-JP175 (PDB ID: 6sjm) [ 31 ], RXRα-honokiol derivative (PDB ID: 5mku) [ 42 ], RXRβ-LG100268 (PDB ID: 1h9u) [ 44 ] and RXRγ-PA, have demonstrated different conformations of helix 12 and the loop preceding this helix, feasibly required for accommodation of different ligands. Since this helix and the loop form a direct interface with helix 2, the small change from Gln270/341 in RXRα/β to His271 in RXRγ, leading to a hydrogen bond with helix 12 Asp449 in the latter, could result in a different degree of flexibility of this region, which may have an indirect effect toward the properties of the ligand-binding pockets.…”
Section: Discussionmentioning
confidence: 99%
“…423 Through N-terminal Nurr1 modulation, C-DIM derivatives may hence exhibit direct effects on Nurr1 for Scheme 9. Nurr1-RXR Heterodimer-Specific RXR Agonists Reported in the Literature 402,403,435,436,438,439 Journal of Medicinal Chemistry example in NFκB transrepression 429 (Figure 4b), but altered Nurr1 protein levels 426 and indirect mechanisms rather than direct Nurr1 transactivation via its LBD appear to dominate the effects. 351 In addition, the antimetabolite 6-MP (91) was identified as a Nurr1 activator from an HTS utilizing a full-length reporter gene assay under the control of the homodimer responsive element in CV1 cells.…”
Section: Nur77 In Pdmentioning
confidence: 99%
“…The synthetic honokiol derivative 89 with a biaryl scaffold demonstrated a greater 25fold selectivity for the Nurr1-RXRα heterodimer (pEC 50 9.1, 129% efficacy) compared to the RXRα homodimer (pEC 50 7.7, 291% efficacy) determined in a BRET assay. 439 The respective cocrystal structure analysis indicated that compact ligands, allowing movement of helix 7 and 11, favor RXRα heterodimerization with Nurr1 (pdb 5MKU), whereas ligands with substituents in the 2′ position on the biaryl scaffold induced pocket expansion with helix 12 movement, resulting in lower binding affinity or antagonistic behavior (pdb 5MKJ) and promoting RXRα homodimerization.…”
Section: Nur77 In Pdmentioning
confidence: 99%
“…Retinoid X receptor (RXR) is a member of nuclear receptor (NR) superfamily, which regulates various physiological metabolism, such as dietary lipid metabolism and nervous system , via forming homodimer or heterodimers with other NRs . Binding of small molecules to the ligand‐binding pocket (LBP) induces the conformational change of ‘AF‐2 interface’, which plays a key role in recognizing the L XX LL motifs located in coactivators .…”
mentioning
confidence: 99%